PERAN PEMERINTAH DESA DALAM MENINGKATKAN PRODUKTIVITAS HASIL PERTANIAN DI DESA KALOLING KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - Bustan, Bustan; Syamsuddin, Syamsuddin; Wahid, Abd (DEMOKRASI, 2025)
This study aims to analyze the role of the Kaloling Village Government in efforts to increase the productivity of agricultural products and identify supporting factors and obstacles in its implementation. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The role of the Kaloling village government is very important in an effort to increase the productivity of agricultural products, considering that the challenges faced by farmers are complex and multidimensional. The village government can play a role as a facilitator who bridges the needs of farmers with programs from the central and regional governments. The results of the study show that the Kaloling Village Government plays an active role in encouraging increased agricultural productivity through extension programs, providing assistance for production facilities (seeds, fertilizers, agricultural tools), agricultural infrastructure development through the Village Fund, as well as support for agricultural institutions and digitalization. The implementation of these programs has had a significant impact on increasing agricultural yields, especially rice and horticultural commodities, with an increase in productivity of 12–15% in the last two years. In addition, village agricultural governance has become more adaptive and open to collaboration with external parties. However, obstacles are still found in the form of limited access to subsidized fertilizers and lack of regeneration of young farmers. Therefore, a sustainable and inclusive village policy is needed so that agricultural productivity can continue to be optimally increased.